Spherical lithium iron manganese phosphate nanoparticles and preparation method thereof
By mixing and adjusting the pH value in a closed reactor, a precursor of lithium iron manganese phosphate was generated, and mixed with a carbon source for grinding and drying. Finally, spherical lithium iron manganese phosphate nanoparticles were calcined under nitrogen protection, which solved the problems of insufficient material performance and complex process in the prior art, and achieved efficient and economical nanoparticle preparation and excellent electrochemical performance.
Patent Information
- Application Number
- CN202211693640.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-28
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-12-28
AI Technical Summary
In the prior art, the low-temperature discharge performance and rate performance indicators of lithium iron manganese phosphate materials still need to be improved, and the preparation process is complex and energy consumption is high, making it difficult to meet the needs of industrial production.
A spherical iron manganese lithium nanoparticles are prepared by mixing lithium, iron, manganese and phosphorus raw materials solutions in a closed reactor, and adding sodium hydroxide solution to adjust the pH value, and then forming a first precursor, mixing it with a carbon source for grinding and drying, forming a second precursor, and finally calcining under nitrogen protection to obtain spherical iron manganese lithium nanoparticles.
The problem of hydrothermal synthesis of non-spherical particles was overcome, and the products produced were highly purified, safer, simple and controllable, suitable for large-scale industrial production, and the rate performance, low-temperature performance and compaction density of the materials were significantly improved.
Smart Images

Figure CN115974036B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery positive electrode material preparation, and in particular to lithium iron manganese phosphate spherical nanoparticles and a preparation method thereof. Background Art
[0002] The main components of lithium-ion batteries include electrolyte, separator, positive and negative electrode materials, etc., among which the mass of positive electrode materials accounts for a large proportion (the mass ratio of positive and negative electrode materials is 3-4:1). Its performance directly affects the performance of lithium-ion batteries, and its cost also directly determines the cost of batteries. Therefore, the positive electrode material of lithium-ion batteries has become a hot topic in lithium-ion battery research.
[0003] Lithium iron phosphate with an olivine structure has attracted great attention as a positive electrode material in the field of secondary lithium-ion batteries due to its safety, low cost and environmental friendliness. However, due to its poor electronic conductivity and only one-dimensional ion transport channel, its ion conductivity is also poor, resulting in the electrochemical performance of this material cannot be effectively exerted. By replacing some iron atoms with manganese atoms to prepare lithium iron manganese phosphate materials, phosphate materials with an olivine structure (LiFe x Mn 1-x PO4), this material presents two discharge platforms of 3.45V and 4.0V. The substitution of manganese theoretically improves the energy density of the material, but the low-temperature discharge performance and rate performance indicators of lithium iron manganese phosphate material still need to be improved.
[0004] The preparation process of the material determines the particle morphology and electrochemical properties of the material. At present, the preparation process of lithium iron manganese phosphate is mainly divided into solid phase reaction method and liquid phase method. The solid phase preparation technology mainly uses iron phosphate, ferrous oxalate, manganese oxalate, and lithium carbonate as raw materials, mixes them with glucose, and calcines them under nitrogen protection to generate lithium iron manganese phosphate. The solid phase synthesis method has a long reaction time, cumbersome operation, low efficiency, and high energy consumption. The particle size distribution of the final product is uneven, and it is easy to agglomerate, and the specific capacity of the obtained product is often not high. For example, Chinese patent application CN104466161A discloses a solid phase synthesis method of lithium iron manganese phosphate material, after the precursor materials iron source, lithium source, phosphorus source, carbon source, and manganese source are mixed in proportion, a dispersant is added for ball milling and drying, and a primary sintering and a secondary sintering are performed under a nitrogen protective atmosphere, respectively, to finally obtain LiMn x Fe 1-x PO4 material. This method requires two calcinations, which takes a long time and consumes a lot of energy. The obtained lithium iron manganese phosphate is agglomerated and has poor dispersion.
[0005] Liquid phase preparation technology mainly refers to hydrothermal / solvothermal synthesis. The hydrothermal preparation of lithium iron manganese phosphate mainly includes dissolving soluble ferrous salt and manganese salt, phosphoric acid and lithium hydroxide in a certain proportion, mixing them in a reactor, and heating them to 120-374°C (critical temperature of water) to obtain lithium iron manganese phosphate crystals. The advantage of the hydrothermal method is that it can prepare nano-sized particles in the direction of the lithium ion channel. The products prepared by this method are mostly flaky and have a low compaction density. It is usually necessary to add a morphology controller during preparation to obtain spherical particles with regular morphology to improve the electrochemical performance of the material. For example, Chinese patent application CN105514430A discloses a spherical manganese iron phosphate lithium cathode material and a preparation method thereof, wherein a lithium source, an iron source, a manganese source, and a phosphorus source are added to deionized water, a carbon source compound is added to the mixed solution, a CTAB template is added thereto and stirred, EDTA is added, a hydrothermal reaction is carried out at 180°C, and a manganese iron phosphate lithium precursor is obtained by filtering and washing, and finally the manganese iron phosphate lithium precursor powder is placed in a tubular calcining furnace for sintering, and the spherical manganese iron phosphate lithium cathode material is obtained by grinding after cooling. However, a template agent needs to be introduced during the formation of the product, and the template agent induces the formation of spherical manganese iron phosphate lithium. The invention has high requirements on the template agent content and the reaction conditions of the environmental solution, and the synthetic hydrothermal process is complicated and not suitable for large-scale industrial production. In addition, since the hydrothermal method is used to prepare lithium iron manganese phosphate, only part of the iron is replaced by manganese, and the process is completely similar. Therefore, with the relevant patents of lithium iron phosphate as a reference, many inventions have been proposed to improve the technology for the problems of preparing lithium iron phosphate by hydrothermal method (the same problem also exists in the preparation of lithium iron manganese phosphate). For example, Chinese patent application CN112723333A discloses a method for improving the low temperature performance and compaction density of lithium iron phosphate, using anhydrous ferrous phosphate and lithium phosphate as raw materials, dispersing them in a water-methanol-ethanol mixture medium, adding polyphenylene ether polymer as a carbon source, grinding under inert gas protection, and then spray drying to form a solid powder, and then the lithium iron phosphate obtained by roasting. However, organic matter is used as a grinding medium in this process, which has higher requirements for the fire and explosion protection of the factory, which is not conducive to reducing costs.
[0006] Chinese patent application CN114597376A discloses a method for preparing lithium iron phosphate material from ferrous phosphate: first, homemade ferrous phosphate containing crystal water is mixed with a carbon source, sintered at low temperature under nitrogen, and part of the crystal water is removed to obtain ferrous phosphate containing a small amount of crystal water; then the ferrous phosphate is evenly mixed with a lithium source, a phosphorus source, and a variety of carbon sources, and adjusted to a suitable iron-phosphorus ratio of 0.960 to 0.975 and a carbon content of 1.5% to 1.8%; then the slurry is dried to obtain a powder; the powder is sintered through a two-stage heating curve, and crushed after natural cooling to obtain a lithium iron phosphate material, and the obtained material has a higher discharge capacity and a longer cycle life. This technology requires calcining in nitrogen in advance to remove the crystal water of hydrated ferrous phosphate, and then the dehydrated ferrous phosphate is mixed with lithium, phosphorus source and organic carbon source in an aqueous medium, and then spray dried and calcined under nitrogen protection. The whole process contains two calcinations, and the operation is slightly complicated and energy-intensive.
[0007] Chinese patent CN101418781A discloses a kind of agglomerated nanostructured lithium iron phosphate positive electrode material and its preparation method. The main technical scheme is to first control the iron-phosphorus ratio of the raw material to 1:1 to prepare a colloidal suspension precursor containing iron and phosphorus, and then mix it with a lithium source and a small amount of phosphorus source to be supplemented and an organic matter as a carbon source in an aqueous medium after filtering, drying and drying, and then prepare lithium iron phosphate by spray drying and nitrogen protection calcination. CN102674291A uses iron source compounds and phosphorus source compounds as raw materials, first prepares nano ferrous phosphate as a precursor, and then mixes ferrous phosphate with lithium source compounds and carbon sources, and calcines twice at 300-450°C and 500-800°C to prepare nano spherical lithium iron phosphate materials. In the above technology, there are also problems such as complicated process, high energy consumption and the inability to ensure that the particles have nano size along the lithium ion channel direction caused by the two drying / calcination.
[0008] In addition, based on the consideration of industrial production process, the mother liquor obtained by hydrothermal preparation of lithium iron phosphate contains lithium sulfate which needs to be recycled. There are also lithium-containing solutions in other lithium salt industries which need to be recycled. If they are recycled to prepare lithium carbonate or lithium hydroxide for battery poles, the cost of the product will increase. The present invention develops a technology to utilize these recycled lithium salt products that are not battery poles, which will be beneficial to reducing the cost of raw materials.
[0009] Therefore, based on both technical and cost considerations, the present invention provides a new synthesis technology to solve the above problems. Summary of the invention
[0010] In order to solve the above problems, the present invention provides a method for preparing spherical lithium iron manganese phosphate nanoparticles. First, refined raw material solutions of lithium, iron and phosphorus sources are mixed in a closed reactor, and then a sodium hydroxide solution is added to adjust the pH value of the reaction system, and then the temperature is increased to generate a first precursor, a small amount of lithium and phosphorus sources are added to the first precursor to adjust the ratio of elements in the material, and a certain amount of soluble organic matter is added as a carbon source, and then the precursor is shaped into a spherical shape by a sand mill, and then spray-dried. While achieving the purpose of drying, a second precursor with a lithium iron manganese phosphate structure is synthesized, and finally calcined under nitrogen protection to obtain a nano lithium iron manganese phosphate positive electrode material with a complete crystal structure and a spherical product morphology.
[0011] The present invention provides a method for preparing spherical lithium iron manganese phosphate nanoparticles, comprising the following steps:
[0012] (1) refining and removing impurities from a mixed solution of a lithium source and a phosphorus source and adding it to a reaction kettle, repeatedly evacuating and filling with nitrogen to expel air, adding a mixed solution of a pure iron source and a manganese source, adjusting the pH value of the reaction system with an alkaline solution, sealing the reaction kettle for reaction, cooling, filtering, and washing the reaction product to obtain a first precursor;
[0013] (2) adding a phosphorus source and a lithium source to the first precursor to adjust the element ratio, then mixing with a carbon source, grinding and drying the mixture to obtain a second precursor;
[0014] (3) calcining the second precursor under nitrogen protection to obtain spherical lithium iron manganese phosphate nanoparticles.
[0015] Furthermore, the lithium source is selected from one of lithium phosphate, lithium hydroxide, lithium carbonate, lithium sulfate, and lithium chloride; the phosphorus source is selected from one of phosphoric acid, lithium phosphate, lithium hydrogen phosphate, lithium dihydrogen phosphate, sodium phosphate, and sodium dihydrogen phosphate; the iron source is selected from ferrous sulfate; the manganese source is selected from manganese sulfate; the alkaline solution is one of sodium hydroxide and ammonia water or a mixture thereof; the carbon source is selected from one or more of glucose, polyethylene glycol, starch, and graphene.
[0016] In step (2), it is necessary to select independent lithium sources and phosphorus sources (ie, lithium phosphate is not selected) to adjust the element ratio.
[0017] More specifically, the concentration of the alkaline solution is 2-5 mol / L.
[0018] Furthermore, after adjusting the pH value in step (1), the molar ratio of the substances in the reaction system is Li:M(Fe+Mn):P=(1.0-3.0):(0.99-1.0):1.0, and the combined concentration of iron and manganese elements is 0.5-1.0 mol / L.
[0019] Specifically, the molar ratio of the iron source to the manganese source is not limited; preferably, the molar ratio of iron and manganese elements is Fe:Mn=3:7 to 7:3.
[0020] Furthermore, in step (1), the pH value is adjusted to a range of 6.0 to 7.5.
[0021] Furthermore, in step (1), the reaction is heated to 60-80° C. under stirring and kept warm for 1-4 hours; and the reaction product is cooled to below 40° C.
[0022] Furthermore, the molar ratio of the substances after adjustment in step (2) is Li:M(Fe+Mn):P=(1.00-3.08):1.0:(1.00-1.06).
[0023] Furthermore, in step (2), the mass ratio of the first precursor to the carbon source is 100:(15-25) on a dry basis.
[0024] Furthermore, in step (2), the grinding frequency is 50 Hz and the grinding time is 30 to 60 min. The material can be shaped in advance by grinding, and the present invention can ensure that the first precursor obtained has a certain density, regular morphology and high sphericity by further accurately controlling the vibration frequency and grinding time of the grinder, thereby ensuring that the morphology can be maintained stable during the roasting process, and obtaining a lithium iron manganese phosphate electrode material with good apparent quality, thereby ensuring that it exerts good electrical properties.
[0025] Furthermore, the drying temperature in step (2) is 260-350° C. Specifically, the drying method includes spray drying, converter drying, and tunnel kiln drying. If spray drying is used, the ground material needs to be mixed with water to prepare a slurry with a solid content of 30-50% (based on the first precursor) before drying.
[0026] Furthermore, in step (3), the calcination temperature is 700-750° C., and the calcination time is 6-9 hours.
[0027] The present invention also provides spherical lithium iron manganese phosphate nanoparticles, which are prepared by the above method.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The preparation method of spherical lithium iron manganese phosphate nanoparticles of the present invention utilizes a lithium source, an iron source, a manganese source, and a phosphorus source to synthesize a first precursor by hydrothermal reaction at a relatively low temperature, and then mixes with a carbon source, grinds and shapes, and dries to generate a spherical second precursor, which is then calcined to obtain spherical lithium iron manganese phosphate nanoparticles. Compared with the general hydrothermal synthesis process, the preparation method of the present invention overcomes the problem of non-spherical lithium iron manganese phosphate nanoparticles synthesized by hydrothermal synthesis, does not require a high temperature and high pressure reaction process, and does not require the addition of a morphology control agent, so the obtained product has a higher purity and higher safety; compared with the general solid phase process, the first precursor obtained in the process of the present invention has a lower decomposition / conversion temperature, and the conversion from the precursor to the positive electrode material lithium iron manganese phosphate can be quickly achieved during drying.
[0030] (2) The preparation method of spherical manganese iron phosphate lithium nanoparticles of the present invention has excellent processing performance. The first precursor generated is easy to grind and shape in a sand mill, and finally a spherical nano-scale material with relatively uniform particle size is obtained, which is not only beneficial to the improvement of the rate performance and low-temperature performance of the material, but also beneficial to the improvement of the compaction density of the material. The prepared spherical manganese iron phosphate lithium nanoparticles have excellent electrochemical performance as positive electrode materials.
[0031] (3) The preparation method of the spherical nano-manganese iron phosphate lithium particles of the present invention has mild operating conditions, no high-pressure operating unit, small equipment investment, simple and controllable process, and good batch stability of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 This is a scanning electron microscope image of the lithium manganese iron phosphate prepared in Example 1 of the present invention;
[0034] Figure 2 The 25°C, 0.2C charge and discharge curve of the battery prepared in Example 1 of the present invention;
[0035] Figure 3 This is a scanning electron microscope image of the lithium manganese iron phosphate prepared in Comparative Example 1 of the present invention;
[0036] Figure 4 This is a scanning electron microscope image of the lithium iron manganese phosphate prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.
[0038] Example 1
[0039] A method for preparing spherical nano-lithium iron manganese phosphate particles comprises the following steps:
[0040] Step 1: Prepare a mixture of lithium, iron, manganese and phosphorus raw materials
[0041] (1) Preparation of phosphorus source and lithium source mixed solution: Take 0.333 kmol of lithium phosphate and add water to a volume of 0.5 m 3 , add 40% sulfuric acid to dissolve it completely, filter and purify it, and then add it to the reactor; take 0.667 kmol of sodium phosphate and dissolve it in 0.3 m 3 After filtering and refining, the mixture is added to the reactor. After repeatedly evacuating the reactor and purging the air in the dead volume with an inert gas (nitrogen), the reactor is sealed to obtain a mixed solution of the lithium source and the phosphorus source;
[0042] (2) Prepare a mixed solution of iron source and manganese source: Take 0.5 kmol of ferrous sulfate heptahydrate and 0.5 kmol of manganese sulfate dihydrate, add water to a volume of 1.0 m 3 , stirring until all dissolved, filtering through a precision filter to obtain a mixed solution of the iron source and the manganese source;
[0043] (3) Preparing a mixed solution of lithium, iron, manganese and phosphorus raw materials: Under stirring at room temperature, the mixed solution of the iron source and the manganese source is added to a reactor containing a mixed solution of the lithium source and the phosphorus source, and stirring is continued for 30 minutes to obtain a mixed solution of lithium, iron, manganese and phosphorus raw materials.
[0044] The molar ratio of the added substances is Li:M(Fe+Mn):P=1.0:1.0:1.0; wherein, Fe:Mn (molar ratio)=1.0:1.0.
[0045] Step 2: Preparation of the first precursor
[0046] Under stirring, add a 5 mol / L sodium hydroxide solution to the mixed solution of lithium, iron, manganese and phosphorus raw materials, adjust the pH value of the reaction system to 6.0, seal the reactor, heat to 60°C, continue stirring and keep warm for 1 hour to react; cool the reaction product to below 40°C, filter, and wash with 80°C hot water until there is no sulfate or chloride ion to obtain a first precursor.
[0047] Step 3: Preparation of the second precursor
[0048] According to the values of lithium, iron-manganese content and phosphorus content in the first precursor, a small amount of lithium carbonate and phosphoric acid are added to adjust the ratio of lithium, iron-manganese content and phosphorus content in the precursor to Li:M(Fe+Mn):P=1.05:1.0:1.02, and then glucose accounting for 15% of the total mass of the first precursor is added. After mixing evenly, the mixed material is sent to a sand mill for grinding at a frequency of 50 Hz for 60 minutes; then the ground material is mixed with water to prepare a slurry with a solid content of 40% (based on the first precursor), and sent to a spray dryer for drying at 320°C to generate a second precursor.
[0049] Step 4: Preparation of spherical lithium iron manganese phosphate nanoparticles
[0050] The second precursor was calcined at 700 °C for 9 h under nitrogen protection to obtain spherical lithium iron manganese phosphate (LiFe 0.5 Mn 0.5 PO4 / C) nanoparticles, the scanning electron microscope image is as follows Figure 1 shown.
[0051] The spherical lithium iron manganese phosphate nanoparticles prepared above were used as the positive electrode material of the battery to test its charge and discharge performance. The specific method is as follows:
[0052] Spherical lithium iron manganese phosphate nanoparticles, acetylene black, and 60% polytetrafluoroethylene emulsion were mixed in a mass ratio of 7:2:1, rolled into a sheet with a thickness of 0.10 mm, and pressed together with aluminum foil, and vacuum dried at 120°C for 12 hours to obtain the battery positive electrode. A button cell was assembled with a metal lithium sheet negative electrode, a 1M LiPF6 solution as the electrolyte, and a 20-micron PE separator and the above positive electrode. The charge and discharge were carried out at 0.2C at 25°C, and the charge and discharge voltage range was 4.5 to 2.3V. The test results are shown in Table 1 and Figure 2 shown.
[0053] like Figure 1 The morphology of the product prepared in this embodiment is shown, and it can be seen that the material is nano-spherical particles with relatively uniform size; the electrochemical performance test results show that as a positive electrode active material, the prepared lithium-ion battery has a higher capacity, higher energy density and higher compaction density.
[0054] Example 2
[0055] A method for preparing spherical nano-lithium iron manganese phosphate particles comprises the following steps:
[0056] Step 1: Prepare a mixture of lithium, iron, manganese and phosphorus raw materials
[0057] (1) Preparation of phosphorus source and lithium source mixed solution: Take 1.0 kmol of lithium sulfate and add water to a volume of 0.5 m 3 , add 40% sulfuric acid to dissolve it completely, filter and purify it, and then add it to the reactor; take 1.0 kmol of sodium phosphate and dissolve it in 0.5 m 3 After filtering and refining, the mixture is added to the reactor. After repeatedly evacuating the reactor and purging the air in the dead volume with an inert gas (nitrogen), the reactor is sealed to obtain a mixed solution of the lithium source and the phosphorus source;
[0058] (2) Prepare a mixed solution of iron source and manganese source: Take 0.6 kmol of ferrous sulfate heptahydrate and 0.4 kmol of manganese sulfate dihydrate, add water to a volume of 1.0 m 3 , stirring until all dissolved, filtering through a precision filter to obtain a mixed solution of the iron source and the manganese source;
[0059] (3) Preparing a mixed solution of lithium, iron, manganese and phosphorus raw materials: Under stirring at room temperature, the mixed solution of the iron source and the manganese source is added to a reactor containing a mixed solution of the lithium source and the phosphorus source, and stirring is continued for 25 minutes to obtain a mixed solution of lithium, iron, manganese and phosphorus raw materials.
[0060] The molar ratio of the added substances is Li:M(Fe+Mn):P=2.0:1.0:1.0; among which, Fe:Mn (molar ratio)=6:4.
[0061] Step 2: Preparation of the first precursor
[0062] Under stirring, add a 3 mol / L sodium hydroxide solution to the mixed solution of lithium, iron, manganese and phosphorus raw materials, adjust the pH value of the reaction system to 7.5, seal the reactor, heat to 80°C, continue stirring and keep warm for 2 hours to react; cool the reaction product to below 40°C, filter, and wash with 90°C hot water until there is no sulfate or chloride ion to obtain a first precursor.
[0063] Step 3: Preparation of the second precursor
[0064] According to the values of lithium, iron-manganese total amount and phosphorus content in the first precursor, a small amount of lithium carbonate and phosphoric acid are added to adjust the ratio of lithium, iron-manganese total amount and phosphorus element in the precursor to Li: M (Fe + Mn): P = 2.06: 1.0: 1.03, and then 20% of starch is added. After mixing evenly, the mixed material is sent to a sand mill for grinding at a frequency of 50 Hz for 40 minutes, and then the ground material is sent to a tunnel kiln through a conveyor belt and dried at 350°C to generate a second precursor.
[0065] Step 4: Preparation of spherical lithium iron manganese phosphate nanoparticles
[0066] The second precursor was calcined at 720°C for 8 h under nitrogen protection to obtain spherical lithium iron manganese phosphate (LiFe 0.6 Mn 0.4 PO4 / C) nanoparticles.
[0067] The electrochemical performance test method is the same as that in Example 1, and the test results are shown in Table 1.
[0068] Example 3
[0069] A method for preparing spherical nano-lithium iron manganese phosphate particles comprises the following steps:
[0070] Step 1: Prepare a mixture of lithium, iron, manganese and phosphorus raw materials
[0071] (1) Preparation of phosphorus source and lithium source mixed solution: Take 3.0 kmol of lithium chloride and add water to a volume of 0.5 m 3 , add 40% sulfuric acid to dissolve it completely, filter and purify it, and then add it to the reactor; take 1.0 kmol of sodium phosphate, add water to a volume of 0.5 m 3 , adding the mixture to a reactor containing lithium chloride under stirring; after purging the air in the dead volume of the reactor with an inert gas, sealing the reactor to obtain a mixed solution of a lithium source and a phosphorus source;
[0072] (2) Prepare a mixed solution of iron source and manganese source: Take 0.4 kmol of ferrous sulfate heptahydrate and 0.6 kmol of manganese sulfate dihydrate, add water to a volume of 1.0 m 3 , stirring until all dissolved, filtering through a precision filter to obtain a mixed solution of the iron source and the manganese source;
[0073] (3) Preparing a mixed solution of lithium, iron, manganese and phosphorus raw materials: Under stirring at room temperature, the mixed solution of the iron source and the manganese source is added to a reactor containing a mixed solution of the lithium source and the phosphorus source, and stirring is continued for 20 minutes to obtain a mixed solution of lithium, iron, manganese and phosphorus raw materials.
[0074] The molar ratio of the added substances is Li:M(Fe+Mn):P=3.0:1.0:1.0; among which, Fe:Mn (molar ratio)=4:6.
[0075] Step 2: Preparation of the first precursor
[0076] Under stirring, add a 2 mol / L sodium hydroxide solution to the mixed solution of lithium, iron, manganese and phosphorus raw materials, adjust the pH value of the reaction system to 7.0, seal the reactor, heat to 70°C, continue stirring and keep warm for 4 hours to react; cool the reaction product to below 40°C, filter, and wash with 100°C hot water until there is no sulfate or chloride ion to obtain a first precursor.
[0077] Step 3: Preparation of the second precursor
[0078] According to the values of the lithium, iron-manganese total amount and phosphorus content in the first precursor, a small amount of lithium carbonate and phosphoric acid are added to adjust the ratio of lithium, iron-manganese total amount and phosphorus in the precursor to Li:M(Fe+Mn):P=3.08:1.0:1.06, and then 25% of graphene is added. After mixing evenly, the mixed material is sent to a sand mill for grinding at a frequency of 50 Hz for 30 minutes; then the ground material is mixed with water to prepare a slurry with a solid content of 50% (based on the first precursor), and sent to a spray dryer for drying at 260°C to generate a second precursor.
[0079] Step 4: Preparation of spherical lithium iron manganese phosphate nanoparticles
[0080] The second precursor was calcined at 750 °C for 6 h under nitrogen protection to obtain spherical lithium iron manganese phosphate nanoparticles (LiFe 0.4 Mn 0.6 PO4 / C).
[0081] The electrochemical performance test method is the same as that in Example 1, and the test results are shown in Table 1.
[0082] Comparative Example 1
[0083] In this comparative example, commercial lithium phosphate is directly used as the lithium source and phosphorus source. Compared with Example 1, no dissolution and impurity removal treatment is performed.
[0084] Step 1: Prepare a mixture of lithium, iron, manganese and phosphorus raw materials
[0085] (1) Preparation of phosphorus source and lithium source mixed solution: Take 0.333 kmol of common industrial grade lithium phosphate and add water to a volume of 0.5 m 3 , add to the reactor; take 0.667 kmol of sodium phosphate and dissolve it in 0.3 m 3 After repeatedly evacuating the air in the dead volume of the reactor with an inert gas (nitrogen), the reactor is sealed to obtain a mixed solution of the lithium source and the phosphorus source;
[0086] (2) Prepare a mixed solution of iron source and manganese source: Take 0.5 kmol of ferrous sulfate heptahydrate and 0.5 kmol of manganese sulfate dihydrate, add water to a volume of 1.0 m 3 , stirring until all dissolved, filtering through a precision filter to obtain a mixed solution of the iron source and the manganese source;
[0087] (3) Preparing a mixed solution of lithium, iron, manganese and phosphorus raw materials: Under stirring at room temperature, the mixed solution of the iron source and the manganese source is added to a reactor containing a mixed solution of the lithium source and the phosphorus source, and stirring is continued for 30 minutes to obtain a mixed solution of lithium, iron, manganese and phosphorus raw materials.
[0088] The molar ratio of the added substances is Li:M(Fe+Mn):P=1.0:1.0:1.0; wherein, Fe:Mn (molar ratio)=1.0:1.0.
[0089] Step 2: Preparation of the first precursor
[0090] Under stirring, add a 5 mol / L sodium hydroxide solution to the mixed solution of lithium, iron, manganese and phosphorus raw materials, adjust the pH value of the reaction system to 6.0, seal the reactor, heat to 60°C, continue stirring and keep warm for 1 hour to react; cool the reaction product to below 40°C, filter, and wash with 80°C hot water until there is no sulfate or chloride ion to obtain a first precursor.
[0091] Step 3: Preparation of the second precursor
[0092] According to the contents of lithium, iron-manganese and phosphorus in the first precursor, a small amount of lithium carbonate and phosphoric acid are added to adjust the ratio of lithium, iron-manganese and phosphorus in the precursor to Li:M(Fe+Mn):P=1.05:1.0:1.02, and then glucose accounting for 15% of the total mass of the first precursor is added. After mixing evenly, the mixed material is sent to a sand mill for grinding at a frequency of 50 Hz for 60 minutes; then the ground material is mixed with water to prepare a slurry with a solid content of 40% (based on the first precursor), and sent to a spray dryer for drying at 320°C to generate a second precursor.
[0093] Step 4: Preparation of lithium iron manganese phosphate nanoparticles
[0094] The second precursor was calcined at 700°C for 9 hours under nitrogen protection to obtain lithium iron manganese phosphate nanoparticles, the scanning electron microscope image of which is shown in FIG. Figure 3 shown.
[0095] The electrochemical performance test method is the same as that in Example 1, and the test results are shown in Table 1.
[0096] like Figure 3 As shown, the particle size and distribution of the product obtained in this comparative example are slightly uneven compared with those in the example, small particles are attached to the surface of large particles, and the particles are seriously aggregated.
[0097] Comparative Example 2
[0098] First, hydrated ferrous (manganese) phosphate is prepared, then mixed evenly with lithium phosphate, glucose is added as a carbon source, spray-dried, and finally calcined. The specific steps are as follows:
[0099] Step 1: Prepare a mixture of iron, manganese and phosphorus raw materials
[0100] (1) Prepare phosphorus source solution: Take 2.0 kmol of sodium phosphate and add water to a volume of 3.0 m 3, stirring until dissolved, adding into the reaction kettle, purging the air in the dead volume in the kettle with an inert gas, and sealing the reaction kettle to obtain a phosphorus source solution;
[0101] (2) Prepare a mixed solution of iron source and manganese source: Take 1.5 kmol of ferrous sulfate heptahydrate and 1.5 kmol of manganese sulfate dihydrate, add water to a volume of 1.5 m 3 , stirring until all dissolved, filtering through a precision filter to obtain a mixed solution of the iron source and the manganese source;
[0102] (3) Preparing a mixed solution of iron, manganese and phosphorus raw materials: Under stirring at room temperature, the mixed solution of the iron source and the manganese source is added to a reactor containing a mixed solution of the phosphorus source, and stirring is continued for 30 minutes to obtain a mixed solution of the iron, manganese and phosphorus raw materials.
[0103] The molar ratio of the added substances is M(Fe+Mn):P=3.0:2.0; wherein, Fe:Mn (molar ratio)=1.0:1.0.
[0104] Step 2
[0105] Under stirring, add a 5 mol / L sodium hydroxide solution to the mixed solution of iron, manganese and phosphorus raw materials, adjust the pH value of the reaction system to 7.5, seal the reactor, heat to 80°C, continue stirring and keep warm for 4 hours to react; filter, wash with 80°C hot water until there is no sulfate or chloride ion, and obtain hydrated ferrous (manganese) phosphate.
[0106] Step 3
[0107] 0.98 kmol of battery-grade lithium phosphate was added to hydrated ferrous (manganese) phosphate, the contents of lithium, iron-manganese total amount and phosphorus element in the mixture were determined, a small amount of lithium carbonate and phosphoric acid were added to adjust the ratio of lithium, iron-manganese total amount and phosphorus element in the precursor to Li:M(Fe+Mn):P=1.05:1.0:1.02, and then glucose accounting for 15% of the total mass of the mixture was added. After mixing evenly, the mixed material was sent to a sand mill for grinding at a speed of 50 Hz for 60 minutes; then the ground material was mixed with water to prepare a slurry with a solid content of 40% (based on the first precursor), and sent to a spray dryer for drying at 320°C.
[0108] Step 4
[0109] The dried material was calcined at 700°C for 9 hours under nitrogen protection to obtain lithium iron manganese phosphate nanoparticles, the scanning electron microscope image of which is shown in the figure Figure 4 shown.
[0110] The electrochemical performance test method is the same as that in Example 1, and the test results are shown in Table 1.
[0111] like Figure 4As shown, the particle morphology of the product prepared in this comparative example is slightly uneven in particle size compared with Example 1.
[0112] Table 1 Electrochemical test results
[0113]
[0114] As shown in Table 1, according to Examples 1-3, the 0.2C specific capacity of the battery prepared by using the spherical lithium iron manganese phosphate nanoparticles prepared by the method of the present invention as the positive electrode material is 155.4-161.6 mAhg -1 The first charge and discharge efficiency is 92.4-94.5%, the energy density and charge and discharge efficiency are high, and the electrochemical performance is good. In Comparative Example 1, ordinary grade commercial lithium phosphate is directly used as the phosphorus source and lithium source without dissolution and purification. Although the morphology of the obtained lithium iron manganese phosphate nanoparticles is similar to that of Example 1 of the present invention, the battery prepared using the particles as the positive electrode active material has a 0.2C specific capacity of only 147.5 mAhg -1 , the first charge and discharge efficiency is only 88.3%, and the performance indicators are poor, mainly because, first of all, the raw materials contain impurities such as calcium, magnesium, trivalent iron and acid insoluble matter that are unfavorable to battery materials. If they are not dissolved and refined, these impurities will participate in the formation of electrode materials, thereby affecting the battery performance; secondly, the phosphate ions in the solid lithium phosphate particles are in an undissolved state. When the first precursor precipitate is generated by reaction, there are fewer free phosphate ions, the concentration of ions participating in the reaction in the solution is low, the generated particles are larger, and the precipitate generated by the reaction easily covers the undissolved lithium phosphate particles, thereby affecting the subsequent reaction of generating the second precursor; in Comparative Example 2, when the iron manganese lithium phosphate positive electrode material obtained by this method is prepared into a battery, its energy density and the first charge and discharge efficiency are not as good as those of the present invention, mainly because in Comparative Example 2, ferrous (manganese) phosphate is first prepared, and the two solids are formed separately and then mixed with the lithium source as a precursor. Compared with the scheme of the present invention in which the first precursor is generated simultaneously in the solution, this method has the problems of uneven mixing and larger particles, thereby affecting the morphology and structure of the active material, and then affecting its electrical properties.
[0115] The above embodiments and comparative examples further illustrate that, using the process of the present invention, the first precursor is prepared by directly mixing the raw materials after dissolution and purification, and the second precursor is obtained after grinding and drying, and then spherical lithium iron manganese phosphate nanoparticles are obtained by roasting. The prepared lithium iron manganese phosphate material is relatively pure, the nanoparticles have high sphericity and regular morphology, excellent electrochemical properties and physical properties, the assembled battery has excellent performance, and the application effect is good.
[0116] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.
Claims
1. A method for preparing spherical lithium iron manganese phosphate nanoparticles, characterized in that: The following steps are involved: (1) After the mixed solution of lithium source and phosphorus source is refined and impurities are removed, it is added into a reaction kettle, and the air is repeatedly discharged by vacuuming and filling with nitrogen, and a mixed solution of pure iron source and manganese source is added, and the pH value of the reaction system is adjusted with an alkaline solution, and the reaction kettle is sealed for reaction, and the reaction product is cooled, filtered, and washed to obtain a first precursor; (2) adding a phosphorus source and a lithium source to the first precursor to adjust the element ratio, then mixing with a carbon source, grinding and drying the mixture to obtain a second precursor; (3) calcining the second precursor under nitrogen protection to obtain spherical lithium iron manganese phosphate nanoparticles; In the step (1), the reaction is heated to 60-80°C under stirring and kept warm for 1-4 hours; the reaction product is cooled to below 40°C; The refining and impurity removal process of the lithium source in step (1) is as follows: after adding water to the lithium source, sulfuric acid with a concentration of 40% is added to dissolve it completely, and after filtering and refining, it is added to the reaction kettle; The pH value adjusted in step (1) is in the range of 6.0 to 7.
5.
2. The method for preparing spherical lithium iron manganese phosphate nanoparticles according to claim 1, characterized in that: The lithium source is selected from one of lithium phosphate, lithium hydroxide, lithium carbonate, lithium sulfate and lithium chloride; The phosphorus source is selected from one of phosphoric acid, lithium phosphate, lithium hydrogen phosphate, lithium dihydrogen phosphate, sodium phosphate, and sodium dihydrogen phosphate; The iron source is ferrous sulfate; the manganese source is manganese sulfate; The alkaline solution is sodium hydroxide, ammonia water or a mixture thereof; The carbon source is selected from one or more of glucose, polyethylene glycol, starch and graphene.
3. The method for preparing spherical lithium iron manganese phosphate nanoparticles according to claim 1, characterized in that: After adjusting the pH value in step (1), the molar ratio of the substances in the reaction system is Li:M(Fe+Mn):P=(1.0-3.0):(0.99-1.0):1.0, and the combined concentration of iron and manganese elements is 0.5-1.0 mol / L.
4. The method for preparing spherical lithium iron manganese phosphate nanoparticles according to claim 1, characterized in that: The molar ratio of the substances after adjustment in step (2) is Li:M(Fe+Mn):P=(1.00-3.08):1.0:(1.00-1.06).
5. The method for preparing spherical lithium iron manganese phosphate nanoparticles according to claim 1, characterized in that: In step (2), the mass ratio of the first precursor to the carbon source is 100:(15-25) on a dry basis.
6. The method for preparing spherical lithium iron manganese phosphate nanoparticles according to claim 1, characterized in that: In step (2), the grinding frequency is 50 Hz, the grinding time is 30 to 60 min, and the drying temperature is 260 to 320° C.
7. The method for preparing spherical lithium iron manganese phosphate nanoparticles according to claim 1, characterized in that: In step (3), the calcination temperature is 700-750° C. and the calcination time is 6-9 hours.
8. A spherical lithium iron manganese phosphate nanoparticle, characterized in that: The product is prepared by the method described in any one of claims 1 to 7.
Citation Information
Patent Citations
Double-layer vane non-principal axis wind power generator
CN101418781A
Preparation method of superfine nanometer lithium iron phosphate electrode material and application thereof
CN102674291A
Solid phase synthesis method for lithium iron manganese phosphate material
CN104466161A
Spherical LiFexMnyPO4 anode material and preparation method thereof
CN105514430A
Method for improving low-temperature performance and compaction density of lithium iron phosphate
CN112723333A